Granting of Building Approval in Lake Border Areas as Reviewed from the Perspective of Indonesian Legislation - Imaldi, Imaldi; Syamsir, Syamsir; Pebrianto, Donny Yusra (Electronic Journal of Education, Social Economics and Technology, 2025)
Development in the lake boundary area is a complex issue because it involves legal, environmental, and spatial planning policy aspects. The granting of Building Permits (PGB) in this area must consider applicable regulations in order to maintain a balance between development interests and protection of the lake ecosystem. This study aims to analyze how local governments grant building permits on lake boundaries and formulate ideal concepts in arranging development in the area in order to realize sustainable ecological protection. This study uses a normative legal approach with a qualitative descriptive analysis method. Data were obtained through a study of laws and regulations governing development in the lake boundary area, such as Law Number 28 of 2002 concerning Buildings, Law Number 26 of 2007 concerning Spatial Planning, and various other derivative regulations. In addition, this study also examines the implementation of PGB policies in several regions to identify obstacles in their implementation. The results of the study indicate that the granting of PGB in the lake boundary area still faces various challenges, such as weak supervision, lack of synchronization of regulations between the central and regional governments, and low awareness of the environmental impacts of development in the area. Therefore, an ideal concept is needed that integrates legal, spatial planning, and environmental sustainability aspects in the policy of granting PGB in the lake border area. The ideal concept in this study includes strengthening regulations and coordination between the central and regional governments, increasing transparency in the PGB granting process, and implementing ecology-based policies to maintain the sustainability of the lake border area. It is hoped that the PGB granting policy can be an effective instrument in maintaining the balance between development and environmental protection in the lake border area in Indonesia.